Antithrombotic Therapy after Deep Venous Intervention - Xiao, Nicholas; Genet, Matthew; Khaja, Minhaj; Desai, Kush R. (Seminars in Interventional Radiology, 2022)
Chronic deep venous disease (CVD) can result in significant morbidity and impact on quality of life due to a spectrum of symptoms, including lower extremity edema, venous claudication, and venous ulcers. CVD can be secondary to both thrombotic and nonthrombotic disease processes, including postthrombotic syndrome from prior deep vein thrombosis (DVT) or iliac vein compression syndrome. Endovascular therapy has become a mainstay therapy for CVD patients, with venous stent placement frequently performed. However, the management of anticoagulation following venous stent placement is not well-studied, with no large trials or consensus guidelines establishing an optimal regimen. The current knowledge gap in antithrombotic therapy is magnified by heterogeneity in practice and data collection, along with incomplete reporting in available studies. Furthermore, most published datasets are antiquated in the setting of rapid evolution in technique and technology available for deep venous intervention. Herein, we summarize the current available literature and offer an approach to anticoagulation and antiplatelet management following deep venous intervention for CVD.
Keywords: interventional radiology; anticoagulation; venous; deep venous thrombosis; postthrombotic syndrome